Bottle demon - Blackmoore, Stephen (DAW book collectors, 2021)
"After being attacked by a demon in the one place he thought he was safe, Eric Carter has been killed, his soul sent to take its place as a stand-in for the Aztec god of death Mictlantecuhtli. But somebody on Earth isn't done with him, yet. Somebody with the power to bring him back from the dead. He doesn't know who, and worse he doesn't know why"--